EVALUASI KETEPATAN PEMBERIAN ALTEPLASE DAN OUTCOME KLINIS PADA PASIEN STROKE ISKEMIK AKUT DENGAN TERAPI TROMBOLISIS DI RUMAH SAKIT X TAHUN 2024 - DAVINA ADIRA NATALIA; Avianti Eka Dewi Aditya Purwaningsih; Francisca Tri Wituningtyas (Fakultas Farmasi Universitas Setia Budi, 2025)
This study aimed to evaluate the timeliness of alteplase administration and clinical outcomes in acute ischaemic stroke patients at Hospital X in 2024. Using a retrospective analytic observational design, data were collected from patients' medical records with a focus on the timeliness of alteplase administration (<4.5 hours) and its impact on clinical outcomes. All patients (100%) received alteplase in a timely manner, according to AHA guidelines, with none receiving therapy after 4.5 hours. The results showed that the timeliness of alteplase administration had a significant effect on clinical outcome, with 90.9% of patients achieving a positive outcome. alteplase administration within the appropriate time window is critical for the clinical recovery of acute ischaemic stroke patients.